2004
DOI: 10.1124/jpet.104.078808
|View full text |Cite
|
Sign up to set email alerts
|

Asiatic Acid, a Triterpene, Induces Apoptosis and Cell Cycle Arrest through Activation of Extracellular Signal-Regulated Kinase and p38 Mitogen-Activated Protein Kinase Pathways in Human Breast Cancer Cells

Abstract: This study first investigates the anticancer effect of asiatic acid in two human breast cancer cell lines, MCF-7 and MDA-MB-231. Asiatic acid exhibited effective cell growth inhibition by inducing cancer cells to undergo S-G2/M phase arrest and apoptosis. Blockade of cell cycle was associated with increased p21/ WAF1 levels and reduced amounts of cyclinB1, cyclinA, Cdc2, and Cdc25C in a p53-independent manner. Asiatic acid also reduced Cdc2 function by increasing the association of p21/WAF1/Cdc2 complex and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
138
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(148 citation statements)
references
References 33 publications
(35 reference statements)
9
138
1
Order By: Relevance
“…Many cytotoxic agents induce a prolonged activation of ERK required for induction of apoptosis or cell cycle arrest (Tang et al, 2002;Xiao and Singh, 2002;Hsu et al, 2005;Chambard et al, 2007). The role of ERK activity in these cellular responses has been confirmed using mitogen-activated protein kinase kinase-1 inhibitors.…”
Section: Discussionmentioning
confidence: 95%
“…Many cytotoxic agents induce a prolonged activation of ERK required for induction of apoptosis or cell cycle arrest (Tang et al, 2002;Xiao and Singh, 2002;Hsu et al, 2005;Chambard et al, 2007). The role of ERK activity in these cellular responses has been confirmed using mitogen-activated protein kinase kinase-1 inhibitors.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, asiatic acid activated phosphorylated p38 kinase and correspondingly induced cell cycle arrest and triggered apoptosis in MCF-7 and MDA-MB-231 cells, respectively. Interestingly, in the same study it was shown that ERK1/2 was activated in asiatic acid-mediated apoptosis in breast cancer cells (Hsu et al, 2005). Similarly, another chemotherapeutic agent, rotenone, which is an inhibitor of the mitochondrial electron transport chain complex I, caused the activation of JNK and p38 and the inactivation of ERK1/2 to induce apoptosis in MCF-7 cells (Deng et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Pentacyclic triterpenoids have been found to have wide-ranging pharmacological effects and in particular AA has been shown to reduce inflammation, inhibit tumor cell proliferation, and induce apoptosis through a mitochondria-dependent pathway [18]. Its anti-cancer efficacy is attributed to its ability to inhibit transcription factor NF-jB, p38 MAP and ERK kinases in a variety of tumor cells [18][19][20][21]. AA induced apoptotic cell death in human hepatoma and malignant glioma cells through enhancing intracellular calcium release [22,23].…”
Section: Asiatic Acidmentioning
confidence: 99%